2021
DOI: 10.1002/edm2.311
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between serum uric acid to high‐density lipoprotein ratio and metabolic syndrome

Abstract: Aims This study aimed to determine a parameter to more easily diagnose metabolic syndrome and predict its probability of occurrence in high‐risk individuals. Methods In this cross‐sectional study, data related to the study population in the Kerman Coronary Artery Disease Risk Factor Study (KERCADRS) were examined. Subjects were divided into two groups with and without metabolic syndrome, and the relevant factors such as the ratios of uric acid to high‐density lipoprotein (HDL) (UHR) in these two groups were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Furthermore, UHR, as a novel marker of metabolic syndrome ( 36 ), has been used to assess type 2 diabetes mellitus ( 16 , 26 ), hepatic steatosis ( 37 ), Hashimoto’s thyroiditis ( 38 ), and the control of MAFLD ( 17 ). UHR was also reported to be associated with poor collateral circulation in chronic total occlusion (CTO) patients and to have important predictive value for cardiovascular mortality in patients living on peritoneal dialysis ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, UHR, as a novel marker of metabolic syndrome ( 36 ), has been used to assess type 2 diabetes mellitus ( 16 , 26 ), hepatic steatosis ( 37 ), Hashimoto’s thyroiditis ( 38 ), and the control of MAFLD ( 17 ). UHR was also reported to be associated with poor collateral circulation in chronic total occlusion (CTO) patients and to have important predictive value for cardiovascular mortality in patients living on peritoneal dialysis ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that UHR is useful for predicting metabolic syndrome. Kocak et al reported that serum UHR is a valuable predictor of metabolic syndrome in Turkish people with diabetes [ 21 ], while Yazdi et al reported that UHR could screen or diagnose metabolic syndrome risks in Iranians without diabetes [ 22 ]. Aktas et al have suggested that UHR can be used for diabetes control evaluations in men with diabetes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increasing prevalence of hyperuricaemia, it should be considered as an important health issue. So far, several studies have emphasized the relationship between the presence of hyperuricaemia and cardiovascular risk factors, including hypertension and metabolic syndrome [10][11][12] as in a recent crosssectional study; Yazdi et al 13 showed that the ratio of uric acid to high-density lipoprotein (HDL) cholesterol is significantly higher in people with metabolic syndrome than in healthy individuals. Despite the similarity of the results of the present study with previous studies, there are also differences.…”
Section: Discussionmentioning
confidence: 99%